Piecewise Analytic Method (PAM) is a New Step in the Evolution of Solving Nonlinear Differential Equation - Abassy, Tamer (International Journal of Applied Mathematical Research, 2019)
In this paper, a new method is introduced for engineers and scientists which can be used for solving highly nonlinear differential equations. The method is called Piecewise Analytic Method (PAM). PAM is used to solve problems which other methods can't solve. The paper also shows how the accuracy and error can be controlled according to the needs.